A unique LAMB3 splice‐site mutation with founder effect from the Balkans causes lethal epidermolysis bullosa in several European countries. (8th August 2016) - Mayer, B.; Silló, P.; Mazán, M.; Pintér, D.; Medvecz, M.; Has, C.; Castiglia, D.; Petit, F.; Charlesworth, A.; Hatvani, Zs.; Pamjav, H.; Kárpáti, S.
Summary: Background: We have encountered repeated cases of recessive lethal generalized severe (Herlitz‐type) junctional epidermolysis bullosa (JEB gen sev) in infants born to Hungarian Roma parents residing in a small region of Hungary. Objectives: To identify the disease‐causing mutation and to investigate the genetic background of its unique carrier group. Methods: The LAMB3 gene was analysed in peripheral‐blood genomic DNA samples, and the pathological consequences of the lethal defect were confirmed by cutaneous LAMB3 cDNA sequencing. A median joining haplotype network within the Y chromosome H1a‐M82 haplogroup of individuals from the community was constructed, and LAMB3 single‐nucleotide polymorphism (SNP) patterns were also determined. Results: An unconventional intronic splice‐site mutation ( LAMB3, c.1133–22G>A) was identified. Thirty of 64 voluntarily screened Roma from the closed community carried the mutation, but none of the 306 Roma from other regions of the country did. The age of the mutation was estimated to be 548 ± 222 years. Within the last year, more patients with JEB gen sev carrying the same unusual mutation have been identified in three unrelated families, all immigrants from the Balkans. Two were compound heterozygous newborns, in Germany and Italy, and one homozygous newborn died in France. Only the French family recognized their Roma background. LAMB3 SNP haplotyping confirmed the link between the apparently unrelated Hungarian, German and Italian male cases, but could not verify the same background in the female newborn from France. Conclusions: The estimated age of the mutation corresponds to the time period when Roma were wandering in the Balkans. Abstract : What's already known about this topic? Premature termination codon mutations in the LAMB3 gene cause lethal generalized severe junctional epidermolysis bullosa. What does this study add? We describe an unusual hidden intronic splice‐site mutation in LAMB3 causing lethal generalized severe junctional epidermolysis bullosa in different European countries. Based on our phylogenetic analysis, we conclude that the mutation originated at the time when the European Roma population wandered the Balkans. What is the translational message? The reported LAMB3 genetic defect represents an unusual splice‐site mutation that might be easily overlooked or not considered as a possible pathogenic candidate. As a recognized pathogenic mutation, it can now be taken into account in the molecular diagnostics of patients with generalized severe junctional epidermolysis bullosa from the Balkans.